Effective therapy of influenza A/H1N1 acute respiratory distress syndrome using extracorporeal membrane oxygenation - Stankiewicz, Adrian; Frank, Marek; Dmitruk, Iwona; Czudzinowicz, Katarzyna; Teodorowski, Wojciech; Walicka-Pyłko, Agnieszka; Matulewicz-Gilewicz, Justyna; Bernacki, Andrzej; Juszczyk, Grzegorz; Matlak, Krzysztof; Siemiątkowski, Andrzej; Sosnowski, Andrzej; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Influenza is an acute viral infectious disease of the respiratory system. It usually proceeds without complications and spontaneously disappears. The disease can also lead to severe complications, particularly in risk groups such as children under 2 years, people with chronic diseases, people over 60 years of age and pregnant women. The paper reported a case of effective treatment of a young pregnant patient with influenza A/H1N1 complicated by acute respiratory distress syndrome (ARDS) using extracorporeal membrane oxygenation (ECMO).